A Mathematical Investigation of Some Economic Effects of Profit Sharing in Socialist Firms - Kornai, J.; Lipták, T. (Econometrica, 1962)
This article examines some economic problems concerned with profit sharing in a Socialist economy. Two alternative systems of incentives have been made the subject of parallel investigations, comparing the effects which each of these systems have on the firm's behavior. We also examine some problems of price regulation. In the investigation both linear and nonlinear programming methods have been used.